2018
DOI: 10.1002/osp4.295
|View full text |Cite|
|
Sign up to set email alerts
|

Fibroblast growth factor 21 and fructose dynamics in humans

Abstract: SummaryObjectiveFructose consumption is a risk factor for metabolic disease. We recently demonstrated that fibroblast growth factor 21 (FGF21), a metabolic hormone involved in lipid and glucose metabolism, is acutely stimulated in humans by 75 g oral fructose, with peak levels occurring 2 h after consumption. This study reports on the dose dependency and reproducibility of the FGF21 response to fructose.MethodsLean, healthy adults drank either five different doses of fructose dissolved in water, each separated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…Fructose ingestions raise FGF21 within 2 hours 3-to 4-fold in humans and a recent study showed a dose-dependent effect of fructose on FGF21 levels, with the highest fructose dose of 75g resulting in at least 100 % increase (2-fold) in all individuals that were studied [196]. This provides evidence for a negative feedback loop regulating sugar consumption, in coherence with mouse data showing that sugar ingestion suppresses FGF21 levels [45,46].…”
Section: Nutrition (Diet) Alters Serum Fgf21 Levelssupporting
confidence: 71%
“…Fructose ingestions raise FGF21 within 2 hours 3-to 4-fold in humans and a recent study showed a dose-dependent effect of fructose on FGF21 levels, with the highest fructose dose of 75g resulting in at least 100 % increase (2-fold) in all individuals that were studied [196]. This provides evidence for a negative feedback loop regulating sugar consumption, in coherence with mouse data showing that sugar ingestion suppresses FGF21 levels [45,46].…”
Section: Nutrition (Diet) Alters Serum Fgf21 Levelssupporting
confidence: 71%
“…The participants were instructed to consume a light meal, such as bread or porridge, >2 h before their scheduled trials. Given that postprandial FGF21 concentrations were affected by fructose consumption in a dose‐dependent manner (Migdal et al., 2018), differences in dietary intake could have affected the FGF21 response in the present study. Future studies on the FGF21 response should standardize or account for dietary intake.…”
Section: Discussionmentioning
confidence: 84%
“…Several population studies have shown that individuals with obesity, type 2 diabetes and metabolic syndrome have higher circulating FGF21 levels , suggesting a state of FGF21 resistance similar to insulin and leptin resistance; this physiological state would therefore be associated with increased risk for the development or worsening of dysmetabolism. Further complicating the study of FGF21 physiology in humans is the wide variability of FGF21 levels within and between individuals, with the precise biological factors contributing to the variability of this hormone remaining unknown .…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of total FGF21 level includes both the cleaved and uncleaved forms of the hormone, while the intact level includes only the uncleaved, active form. The ratio of intact‐to‐total FGF21 remains unchanged over the course of a 75 g of OFTT , but it is not known whether the ratio of intact‐to‐total FGF21 changes in response to ongoing high‐fructose exposure. The present study demonstrates that the baseline ratio of intact‐to‐total FGF21 remains stable after 2 weeks of high‐fructose consumption, while the stimulated ratio trends towards an increase; larger studies are required to determine whether this change is significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation